2011
DOI: 10.1002/qua.23096
|View full text |Cite
|
Sign up to set email alerts
|

Analytical arbitrary ℓ‐wave solutions of the manning–rosen potential in the tridiagonalization program

Abstract: By working in a complete square integrable basis that carries a tridiagonal matrix representation of the wave operator, the arbitrary '-wave solutions of the Schrö dinger equation for the Manning-Rosen potential is investigated with an approximation of centrifugal term. The resulting three-term recursion relation for the expansion coefficients of the wavefunction is presented. The bound-state wavefunctions are expressed in terms of the Jocobi polynomial, and the discrete spectrum of the bound states is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…from which a tridiagonal matrix representation for the wave operator, ϕ m |H − E|ϕ n , is achievable by imposing the following conditions on the last term, which should either be eliminated by choosing (α, β) = 1 2 (ν, µ) or be proportional to δ m,n−1 ,which requires (α, β) be 1 2 (ν + 1, µ) or 1 2 (ν, µ + 1). It is shown that the last two cases correspond to the hyperbolic Rosen-Morse potential and the hyperbolic Pöschl-Teller potential [26,28]. Hence, we will only be concerned with the first case.…”
Section: The Deformed Hyperbolic Single-wave Potentialmentioning
confidence: 99%
“…from which a tridiagonal matrix representation for the wave operator, ϕ m |H − E|ϕ n , is achievable by imposing the following conditions on the last term, which should either be eliminated by choosing (α, β) = 1 2 (ν, µ) or be proportional to δ m,n−1 ,which requires (α, β) be 1 2 (ν + 1, µ) or 1 2 (ν, µ + 1). It is shown that the last two cases correspond to the hyperbolic Rosen-Morse potential and the hyperbolic Pöschl-Teller potential [26,28]. Hence, we will only be concerned with the first case.…”
Section: The Deformed Hyperbolic Single-wave Potentialmentioning
confidence: 99%